Analisis Peluang dan Dampak Dekolonialisasi Kurikulum Sejarah Indonesia - Subair, Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Decolonising Indonesia's history curriculum is important in the context of forming an inclusive and accurate national identity. The background of this research focuses on the influence of colonialism on the presentation of history in educational curricula that still prioritise colonial perspectives. This research aims to explore how the history curriculum can be decolonised to reflect a more just and diverse narrative. This research uses a qualitative approach with a case study of history curriculum studies, aiming to explore and compare the effects of a curriculum with a colonial perspective and a decolonial curriculum proposal for the history curriculum, in the context of the Merdeka curriculum and Curriculum 2013. The results showed that there is a need to revise the history curriculum to include local perspectives and pay attention to marginalised voices in historical narratives. In addition, this research identifies various strategies that can be applied in developing a more inclusive and contextualised curriculum, including the involvement of local communities in the preparation of teaching materials. The findings are expected to make a significant contribution to history education reform in Indonesia